Long‐term pulmonary disease among Swiss childhood cancer survivors. Issue 1 (4th September 2017) - Kasteler, Rahel; Weiss, Annette; Schindler, Matthias; Sommer, Grit; Latzin, Philipp; von der Weid, Nicolas X.; Ammann, Roland A.; Kuehni, Claudia E.; ,
Abstract: Background: Pulmonary diseases are potentially severe late complications of childhood cancer treatment that increase mortality risk among survivors. This nationwide study assesses the prevalence and incidence of pulmonary diseases in long‐term childhood cancer survivors (CCS) and their siblings, and quantifies treatment‐related risks. Methods: As part of the Swiss Childhood Cancer Survivor Study, we studied CCS who were diagnosed between 1976 and 2005 and alive at least 5 years after diagnosis. We compared prevalence of self‐reported pulmonary diseases (pneumonia, chest wall abnormalities, lung fibrosis, emphysema) between CCS and their siblings, calculated cumulative incidence of pulmonary diseases using the Kaplan–Meier method, and determined risk factors using multivariable logistic regression. Results: CCS reported more pneumonias (10% vs. 7%, P = 0.020) and chest wall abnormalities (2% vs. 0.4%, P = 0.003) than siblings. Treatment with busulfan was associated with prevalence of pneumonia (odds ratio [OR] 4.0, 95% confidence interval [CI] 1.1–14.9), and thoracic surgery was associated with chest wall abnormalities and lung fibrosis (OR 4.1, 95% CI 1.6–10.7 and OR 6.3, 95% CI 1.7–26.6). Cumulative incidence of any pulmonary disease after 35 years of follow‐up was 21%. For pneumonia, the highest cumulative incidence was seen in CCS treated with both pulmotoxic chemotherapy and radiotherapy to the thorax (23%). Conclusion: This nationwide study in CCS found an increased risk for pulmonary diseases, especially pneumonia, while still young, which indicates that CCS need long‐term pulmonary follow‐up.